Monthly Trauma Training and Simulation Are Associated With Improved Resident Skill and Leadership. Issue 1 (January 2022) - Park, Caroline; Lin, I-Chun; Grant, Jennifer L.; Dultz, Linda A.; Johnson, Della; Jeter, Shannon; Abdelfattah, Kareem; Luk, Stephen; Cripps, Michael; Dumas, Ryan P.
Abstract : BACKGROUND: Training for trauma procedures has been limited to infrequent courses with little data on longitudinal performance, and few address procedural and leadership skills with granular assessment. We implemented a novel training program that emphasized an assessment of trauma resuscitation and procedural skills. OBJECTIVE: This study aimed to determine whether this program could demonstrate improvement in both skill sets in surgical trainees over time. METHODS: This was a prospective, observational study at a Level I trauma center between November 2018 and May 2019. A procedural skill and simulation program was implemented to train and evaluate postgraduate year (PGY) 1–5 residents. All residents participated in an initial course on procedures such as tube thoracostomy and vascular access, followed by a final evaluation. Skills were assessed by the Likert scale (1–5, 5 noting mastery). PGY 3s and above were additionally evaluated on resuscitation. A paired t test was performed on repeat learners. RESULTS: A total of 40 residents participated in the structured procedural skills and simulation program. Following completion of the program, PGY-2 scores increased from a Mdn [interquartile range, IQR] 3.0 [2.5–4.0] to 4.5 [4.2–4.5]. The PGY-3 scores increased from a Mdn [IQR] 3.95 [3.7–4.6] to 4.8 [4.6–5.0]. Eighteen residents underwent repeat simulation training, with Mdn [IQR] score increases in PGY 2s (3.7 [2.5–4.0] to end score 4.47 [4.0–4.5], p = .03) and PGY 3s (3.95 [3.7–4.6] to end score 4.81 [4.68–5.0], p = .04). Specific procedural and leadership skills also increased over time.